Heun Method Using to Solve System of NonLinear Functional Differential Equations (Baghdad Science Journal, 2025)
In this paper Heun method has been used to find numerical solution for first order nonlinear functional differential equation. Moreover, this method has been modified in order to treat system of nonlinear functional differential equations .two numerical examples are given for conciliated the results of this method.